ABBV-105, a selective and irreversible inhibitor of Bruton's tyrosine kinase, is efficacious in multiple preclinical models of inflammation. Issue 3 (4th May 2019) - Goess, Christian; Harris, Christopher M.; Murdock, Sara; McCarthy, Richard W.; Sampson, Erik; Twomey, Rachel; Mathieu, Suzanne; Mario, Regina; Perham, Matthew; Goedken, Eric R.; Long, Andrew J.
Abstract: Objectives: Bruton's tyrosine kinase (BTK) is a non-receptor tyrosine kinase required for intracellular signaling downstream of multiple immunoreceptors. We evaluated ABBV-105, a covalent BTK inhibitor, using in vitro and in vivo assays to determine potency, selectivity, and efficacy to validate the therapeutic potential of ABBV-105 in inflammatory disease. Methods: ABBV-105 potency and selectivity were evaluated in enzymatic and cellular assays. The impact of ABBV-105 on B cell function in vivo was assessed using mechanistic models of antibody production. Efficacy of ABBV-105 in chronic inflammatory disease was evaluated in animal models of arthritis and lupus. Measurement of BTK occupancy was employed as a target engagement biomarker. Results: ABBV-105 irreversibly inhibits BTK, demonstrating superior kinome selectivity and is potent in B cell receptor, Fc receptor, and TLR-9-dependent cellular assays. Oral administration resulted in rapid clearance in plasma, but maintenance of BTK splenic occupancy. ABBV-105 inhibited antibody responses to thymus-independent and thymus-dependent antigens, paw swelling and bone destruction in rat collagen induced arthritis, and reduced disease in an IFNα-accelerated lupus nephritis model. BTK occupancy in disease models correlated with in vivo efficacy. Conclusion: ABBV-105, a selective BTK inhibitor, demonstrates compelling efficacy in pre-clinical mechanistic models of antibody production and in models of rheumatoid arthritis and lupus.